Assessing the potential to reduce deaths and injuries from mass shootings through restrictions on assault weapons and other high-capacity semiautomatic firearms - Koper, Christopher S. (Criminology & public policy, 2020)
Research This article examines the use, impacts, and regulation of assault weapons and other high-capacity semiautomatic firearms as they pertain to the problem of mass shootings in the United States. High-capacity semiautomatics (which include assault weapons as a subset) are used in between 20% and 58% of all firearm mass murders, and they are used in a particularly high share of public mass shootings. Mass shootings perpetrated with these firearms result in substantially more fatalities and injuries than do attacks with other firearms, and these differences are especially pronounced for the number of victims with nonfatal gunshot injuries. The federal ban on assault weapons and large-capacity (>10 rounds) ammunition magazines of 1994 had exemptions and loopholes that limited its short-term effects, but its expiration in 2004 was followed by an increase in the use of these weapons in mass shootings and other crimes. Growing evidence suggests that state-level restrictions on large-capacity magazines reduce mass shootings, but further research is needed on the implementation and effects of these laws. Policy Implications Restrictions on large-capacity magazines are the most important provisions of assault weapons laws in part because they can produce broader reductions in the overall use of high-capacity semiautomatics that facilitate high-volume gunfire attacks. Data on mass shooting incidents suggest these magazine restrictions can potentially reduce mass shooting deaths by 11% to 15% and total victims shot in these incidents by one quarter, likely as upper bounds. It may take several years for the effects of these laws to be fully realized, however, depending on their specific provisions, especially with regard to treatment of pre-ban weaponry.